2009
DOI: 10.1002/jso.21273
|View full text |Cite
|
Sign up to set email alerts
|

Nodal stage of stage III colon cancer: The impact of metastatic lymph node ratio

Abstract: Purpose:We assessed which classification of lymph node metastasis better predicted outcomes in patients with colorectal carcinoma. Methods: We identified 318 patients (176 men) with stage III colon cancer who underwent curative resection. The number of LNs dissected, LNR, and disease-free survival time, were analyzed. Lymph node disease was stratified by the American Joint Committee on Cancer staging and LNR, with the latter categorized into groups with LNR <0.059 (n ¼ 67), 0.059-0.23 (n ¼ 171), and >0.23 (n ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
(29 reference statements)
2
27
0
3
Order By: Relevance
“…In the literature on the number of LNs retrieved, as shown in Table 1, 12 of 17 articles assessed 12 or more nodes [26,28,34,5053,5761] . In many studies that were reviewed in this editorial, more than 12 LNs were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature on the number of LNs retrieved, as shown in Table 1, 12 of 17 articles assessed 12 or more nodes [26,28,34,5053,5761] . In many studies that were reviewed in this editorial, more than 12 LNs were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, numerous studies on LNRs in CRC patients were published [28,34,5761] . Vather et al [57] reported the significance of LN evaluation in 4309 stage Ⅱ and stage Ⅲ colon cancer patients.…”
Section: Lnr In Crcmentioning
confidence: 99%
“…Among these, the LNR is probably the best investigated and particularly pertains to substaging of stage III disease [15,18,19,20,21,22,23,24,25,26]. The LNR, defined as the ratio of the number of positive nodes over the total number of examined nodes, was proposed to stratify outcome in stage III patients.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A MEDLINE search was conducted to provide an overview of the literature concerning the prognostic impact of the LNR using the keywords "colorectal cancer" and "lymph node ratio." Of these 21 articles, 7 reports, including the present study, addressed the relationship between the prognostic impact of the LNR and the number of LNs examined.…”
Section: Discussionmentioning
confidence: 99%
“…9 To date, several other studies have reported the prognostic signifi cance of the LNR in colorectal cancer. 3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] It has also been suggested that the LNR can predict survival more accurately than the number of positive LNs. 3,4,11,13,16,19 Furthermore, the application of the LNR, together with the TNM system, may be more predictive of cancer recurrence and survival.…”
Section: Introductionmentioning
confidence: 99%